2005
DOI: 10.1016/j.jenvp.2005.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the acceptability of energy policies: A test of VBN theory

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
732
10
33

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 913 publications
(884 citation statements)
references
References 36 publications
56
732
10
33
Order By: Relevance
“…Taking the example of NAT applications, some researchers measured the various model variables on a general level [49,92], while others measured them on a specific level [33,93,122]. Pronello and Camusso [35] used both specific and general attitudes to segment the market.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking the example of NAT applications, some researchers measured the various model variables on a general level [49,92], while others measured them on a specific level [33,93,122]. Pronello and Camusso [35] used both specific and general attitudes to segment the market.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale is that pro-social behaviour depends on the activation of personal moral norms, which are triggered once individuals expect a negative outcome to a given situation (problem awareness [PA] and adverse consequences [AC]) and when they believe their action may have a role in reducing this threat (ascription of responsibility [AR]). It seems that there is confusion among researchers about how to interpret the causal relationship between the variables: at least three approaches have been proposed in the literature to deal with such variables: (1) the relationship between Personal Norms (PN) and Behaviour is moderated by Problem Awareness (PA) and Ascription of Responsibility (AR) [90,91]; (2) Problem Awareness (PA) influences Ascription of Responsibility (AR), which in turn influences Personal Norms (PN) and PN influence behaviour [32,49,92,93]; (3) both Problem Awareness (PA) and Ascription of Responsibility (AR) influence PN, while PN, in turn, influence behaviour [67,94]. The first interpretation refers to a moderator model, while the other two interpretations imply a causal or mediation model.…”
Section: Trans Theoretical Model (Ttm)mentioning
confidence: 99%
“…It is also key to consider public-sphere (i.e., sociopolitical) actions, such as policy support, lobbying, voting, and engaging in community action to instigate or support change at the wider, structural level (e.g., Steg et al, 2005;Schuitema et al, 2010).…”
Section: (D) Focusing On Environmentally Significant Behaviors Inclumentioning
confidence: 99%
“…Individuals having an outward environmental attitude can demonstrate various types of behaviour, which can have a direct effect on public policy-making (e.g., putting pressure on political parties, increasing bargaining power of environmental lobbies, becoming a member of an environmental group), but an indirect effect on the natural environment (e.g., new policy on environmental preservation, new rules for animal hunting, harmonization with international environmental standards) (Dietz et al, 1998;Stern, 2000). A number of empirical studies found that consumer attitudes about the state of the natural environment are positively associated with such behaviour (Stern et al, 1999;Steg et al, 2005;Kilbourne & Pickett, 2008). Hence, the following hypothesis can be made:…”
mentioning
confidence: 99%